Forest pedagogy in a primary education and its perception by the pedagogues - Kollárová Dana (University of Kragujevac - Faculty of Pedagogy, Užice, 2021)
Currently, elementary education teachers and tutors in Slovakia express massive interest in collaboration with forest pedagogues. This collaboration focuses on fulfilling educational standards and meeting educational objectives tight to the topics of the forest environment. These are mainly the topics from the subjects of Human and nature, Human and society, Human and the world of labour. The object of the research was teachers' opinions on collaboration with forest pedagogues and the impact of forest pedagogy on the educational process.